Metals in Past Societies: A Global Perspective on Indigenous African Metallurgy - Chirikure, Shadreck (Springer, 2015)
This book seeks to communicate to both a global and local audience, the key attributes of pre-industrial African metallurgy such as technological variation across space and time, methods of mining and extractive metallurgy and the fabrication of metal objects. These processes were transformative in a physical and metaphoric sense, which made them total social facts. Because the production and use of metals was an accretion of various categories of practice, a chaine operatoire conceptual and theoretical framework that simultaneously considers the embedded technological and anthropological factors was used.